2008
DOI: 10.1128/aac.00381-08
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Doripenem, a Carbapenem for the Treatment of Challenging Infections Caused by Gram-Negative Bacteria, against Recent Clinical Isolates from the United States

Abstract: Doripenem, a 1␤-methylcarbapenem, is a broad-spectrum antibiotic approved for the treatment of complicated urinary tract and complicated intra-abdominal infections. An indication for hospital-acquired pneumonia including ventilator-associated pneumonia is pending. The current study examined the activity of doripenem against recent clinical isolates for the purposes of its ongoing clinical development and future longitudinal analysis. Doripenem and comparators were tested against 12,581 U.S. clinical isolates c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
41
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 34 publications
6
41
1
1
Order By: Relevance
“…Doripenem for injection is a sterile, synthetic, parenteral antibiotic of the carbapenem class of ␤-lactam antibiotics with broadspectrum, potent, antibacterial activity against aerobic and anaerobic Gram-negative and Gram-positive pathogens, including extended-spectrum ␤-lactamase-producing Enterobacteriaceae and Pseudomonas aeruginosa (11)(12)(13)(14)(15)(16)(17)(18)(19). It exerts its activity by targeting penicillin-binding proteins to inhibit the biosynthesis of the bacterial cell wall.…”
mentioning
confidence: 99%
“…Doripenem for injection is a sterile, synthetic, parenteral antibiotic of the carbapenem class of ␤-lactam antibiotics with broadspectrum, potent, antibacterial activity against aerobic and anaerobic Gram-negative and Gram-positive pathogens, including extended-spectrum ␤-lactamase-producing Enterobacteriaceae and Pseudomonas aeruginosa (11)(12)(13)(14)(15)(16)(17)(18)(19). It exerts its activity by targeting penicillin-binding proteins to inhibit the biosynthesis of the bacterial cell wall.…”
mentioning
confidence: 99%
“…Doripenem is a parenteral carbapenem with in vitro microbiological activity against a broad spectrum of clinically important Gram-positive and Gram-negative pathogens (9,14,23). It is approved for complicated intra-abdominal and complicated urinary tract infections (UTI) in the United States and in Europe, where it is also approved for nosocomial pneumonia (15).…”
mentioning
confidence: 99%
“…Analysis of 1,772 clinical www.intechopen.com E. coli isolates (many from complicated UTIs) found that 99.8% of them were susceptible to doripenem, including all 30 ESBL-producers (Pillar et al, 2008). Analysis of 6 Phase III clinical trials demonstrated that doripenem was as effective as levofloxacin, imipenem, meropenem and piperacillin-tazobactam in treatment of patients with complicated UTIs due to ciprofloxacin-resistant and ESBL-producing Enterobacteriaceae (largely UPEC) (Kaniga et al, 2010).…”
Section: Newer Uti Therapies 331 Recently Approved Therapiesmentioning
confidence: 99%